PENGARUH PEMBERIAN KELAKAI (STENOCHLAENA PALUSTRIS) TERHADAP PENINGKATAN KADAR HEMOGLOBIN IBU HAMIL DI KLINIK KASIH IBU KECAMATAN DELI TUA - Sari, Husna; Hayati, Erlina; Sari, Putri Mayang; ., Sarmana (JURNAL ILMIAH DHDT - KEBIDANAN, 2023)
Anemia often occur due to iron deficiency due to the increase in blood volume in pregnant women to meet iron needs. one alternative for Fulfill needs substance iron could conducted with consumption vegetables that contain substance iron in the food menu . Kelakai is plant type the usual nails utilized as vegetables. Kelakai contain substance iron on leaves behavior (291.32 mg/100 grams) Substance iron (Fe) is a related factors with formation cell blood red and hemoglobin in blood . The aim of the research is to prove the effect of giving kelakai (Stenochlaena palustris) on increasing hemoglobin levels in pregnant woman at Kasih Ibu clinic. This research uses quasi-experimental with one..group..pretest and posttest..design . Data..analyzed..using the T-Test. The sampling technique in this study used a purposive hemoglobin sampling technique using the HB Quick Check tool. 15 respondents were Pregnant women who experience anemia consume 100gr kelakai (Stenochlaena Palustris) per day for 7 days. T-Test results obtained t value 8.049 and value P Value 0.000 < 0.05. The results of the study concluded that giving kelakai (Stenochlaena palustris) had an effect on increasing hemoglobin in pregnant women.